Design and development of outstanding strain properties in NBT-based lead-free piezoelectric multilayer actuators by grain-orientation engineering. (1st March 2023) - Liu, Kai; Liu, Fafu; Zhang, Wu; Dou, Zhanming; Ma, Weigang; Samart, Chanatip; Takesue, Naohisa; Tan, Hua; Fan, Pengyuan; Ye, Zuo-Guang; Zhang, Haibo
Abstract: (Na1/2 Bi1/2 )TiO3 -based (NBT-based) piezoelectric multilayer actuators (MLAs) have attracted massive attention to replacing conventional lead-based piezoelectric devices recently in the fields of micro-actuation and micro-manipulation due to serious concerns of the lead element to the environment and human beings. To simultaneously achieve a high-strain output and effective co-firing with 70Ag/30Pd internal electrodes, we applied a grain orientation engineering approach to prepare a (001)c -textured NBT-based ((Na1/2 Bi1/2 )0.935 Ba0.065 Ti0.978 (Fe1/2 Nb1/2 )0.022 O3 ) MLA by low-temperature sintering. Notably, the textured MLA achieved a high texturing degree ( F 00l  = 94%) at a low sintering temperature (1000 °C) and an excellent strain level of 0.46% (at 60 kV/cm) which is about 2.6 times as high as that of the non-textured counterpart. The outstanding strain performance can be explained by the optimized composition/phase selection, the lattice distortion, and the strong crystallographic anisotropy induced by the introduced NaNbO3 templates. The analysis of mechanical properties and fracture micromorphology reveals the effects of grain orientation engineering on the fracture strength and Young's modulus of bulk ceramics and MLAs. To explore potential practical applications, the temperature stability and electric fatigue of the MLAs were investigated. With the design and fabrication of the textured NBT-based MLA, this work provides a new paradigm for the applications of lead-free piezoceramics by appropriate phase controlling and grain-orientation engineering. Graphical abstract: Image, graphical abstract